Synthesis paradigm and applications of silver nanoparticles (AgNPs), a review - Beyene, Hayelom Dargo (Sustainable Materials and Technologies, 2017)
Nanoscience is an inspiring and influential discipline of science which have accessible numerous novel and cost-effective yields and applications. Currently, nanotechnology research has been empowering more in agricultural sector, food process and medicinal industries. The surface area to volume ratio of nanoparticles is quite large which have 1–100 nm size. Nanomaterials have superior bioavailability than larger particles, resulting in greater utilization in single cells, tissues and organs. Referable to the growing demand of nanoparticles, it is essential to build up synthetic method which is profitable, environmentally sustainable and which can substitutes with effective and competent technology to synthesis environmentally benign nanoparticles (NPs). Nanomaterials are “deliberately engineered” to direct the enhancement of special properties at the nanoscale. Nanoparticles have been known to be used for abundant physical, biological, and pharmaceutical applications. Nano-silver is the most studied and utilized nanoparticle. Silver nanoparticles (AgNPs) have been the topics of researchers because of their unique properties. Thus, this review presents various synthesis methods of AgNPs and its application in different sectors.